Educare oltre confine. Storie narrazioni intercultura - Nanni, Silvia (La melagrana - Open Access, 2015)
The volume is based upon the pedagogical intercultural project "L'Aquila oltre i confini", a set of educational programs on the active and participatory citizenship, on the prevention and the overcoming of all forms of discrimination and intolerance. The path propose methodologies that can be contextualized within schools and universities and used for training of educational and social professionals.